2022
DOI: 10.1007/s40843-022-2085-4
|View full text |Cite
|
Sign up to set email alerts
|

Boosting visible-light-driven water splitting over LaTaON2via Al doping

Abstract: LaTaON 2 is an attractive visible-light-active photocatalyst for water splitting due to its broad visible light absorption as far as 650 nm and proper band edge positions. Notwithstanding these promising properties, LaTaON 2 generally exhibits poor photocatalytic activity because of its high defect concentration that severely hinders charge separation. Here, LaTaON 2 has been modified by doping Al into the Ta sublattice, i.e., LaTa 1−x Al x O 1+y N 2−y (0 ≤ x ≤ 0.20). Al doping not only inhibits the defect con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…Metal oxynitrides and nitrides have received significant attention as catalysts particularly for water splitting, 28 electrocatalytic reduction of nitrogen to ammonia, 29 and CO 2 photoreduction. 30 Recent research by Wahab et al investigates the possibility of utilizing early-transition metal-based oxides/nitrides as an efficient electrocatalyst for hydrogen generation from saline water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal oxynitrides and nitrides have received significant attention as catalysts particularly for water splitting, 28 electrocatalytic reduction of nitrogen to ammonia, 29 and CO 2 photoreduction. 30 Recent research by Wahab et al investigates the possibility of utilizing early-transition metal-based oxides/nitrides as an efficient electrocatalyst for hydrogen generation from saline water.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that the introduction of Fe can dramatically decrease the internal resistance of the cell, 23 thereby suppressing the anodic overpotential of the cell. Addition of Fe also achieves improvements in the H 2 oxidation 25,26 Metal oxynitrides and nitrides have received signicant attention as catalysts particularly for water splitting, 28 electrocatalytic reduction of nitrogen to ammonia, 29 and CO 2 photoreduction. 30 Recent research by Wahab et al investigates the possibility of utilizing early-transition metal-based oxides/ nitrides as an efficient electrocatalyst for hydrogen generation from saline water.…”
Section: Introductionmentioning
confidence: 99%
“…Wan et al [16] have made a CdS/PbTiO 2 /TiO 2 heterostructure catalyst with combined interfacial electrical and ferroelectric fields which can efficiently separate charges and lead to two orders of magnitude improvement of photocatalytic hydrogen production. In addition, Yang et al [17] have doped Al into the lattice of LaTaON 2 , which maintains the light absorption property, inhibits the defect concentration, and increases the surface hydrophilicity of the catalysts, leading to much enhanced photocatalytic water oxidation performance. Yin et al [18] have prepared a CoO x /Ni:COOH bilayer-protected n-Si photoanode which is stable under oxygen evolution with improved onset potential and photocurrent density.…”
mentioning
confidence: 99%